Object Detection Model Training Framework for Very Small Datasets Applied to Outdoor Industrial Structures - Baharuddin M.Z.; How D.N.T.; Sahari K.S.M.; Abas A.Z.; Ramlee M.K. (Springer Science and Business Media Deutschland GmbH, 2023)
Computer vision; Convolutional neural networks; Deep neural networks; Digital devices; Feature extraction; Image enhancement; Inspection; Object recognition; Convolutional neural network; Deep learning; Detection models; Industrial inspections; Industrial structures; Model training; Objects detection; Retinanet; Small data set; Training framework; Object detection